Risk management in enterprise activity in current economic conditions (Journal of Economic Research & Business Administration, 2016)
The article deals with the enterprise risk-management problems. Theauthors analyze development of assessment methodology and managementof risks of innovative projects and the basic levels of risk management;they give the matrix of key components of the enterprise risk managementprocess. This concept allows to deal successfully with incipientproblems and use the opportunities increasing the enterprise potential.
Keywords: enterprise risks; enterprise risk management; concept of risk management; methods of risk management.